Nicotinamide adenine dinucleotide phosphate oxidase 2 deletion attenuates polyhexamethylene guanidine-induced lung injury in mice - Yoon Cho; Seulgi Jeon; Sung-Hwan Kim; Hyeon-Young Kim; Bumseok Kim; Mi-Jin Yang; Jinhyung Rho; Moo-Yeol Lee; Kyuhong Lee; Min-Seok Kim (Heliyon, 2024)
Inhalation of polyhexamethylene guanidine phosphate (PHMG) can cause pulmonary fibrosis. Nicotinamide adenine dinucleotide phosphate (NADPH) oxidases (Nox) are enzymes that produce reactive oxygen species, which may be involved in tissue damage in various lung diseases. To investigate whether the Nox2 isoform of Nox is involved in the progression of PHMG-induced lung damage, we studied the contribution of Nox2 in PHMG-induced lung injury in Nox2-deficient mice. We treated wild-type (WT) and Nox2 knockout mice with a single intratracheal instillation of 1.1 mg/kg PHMG and sacrificed them after 14 days. We analyzed lung histopathology and the number of total and differential cells in the bronchoalveolar lavage fluid. In addition, the expressions of cytokines, chemokines, and profibrogenic genes were analyzed in the lung tissues. Based on our results, Nox2-deficient mice showed less PHMG-induced pulmonary damage than WT mice, as indicated by parameters such as body weight, lung weight, total cell count, cytokine and chemokine levels, fibrogenic mediator expression, and histopathological findings. These findings suggest that Nox2 may have the potential to contribute to PHMG-induced lung injury and serves as an essential signaling molecule in the development of PHMG-induced pulmonary fibrosis by regulating the expression of profibrogenic genes.